2022
DOI: 10.3390/atmos13030443
|View full text |Cite
|
Sign up to set email alerts
|

Wind Speed Statistics from a Small UAS and Its Sensitivity to Sensor Location

Abstract: With the increase in the use of small uncrewed aircraft systems (UAS) there is a growing need for real-time weather forecasting to improve the safety of low-altitude aircraft operations. This will require integration of measurements with autonomous systems since current available sampling lack sufficient resolution within the atmospheric boundary layer (ABL). Thus, the current work aims to assess the ability to measure wind speeds from a quad-copter UAS and compare the performance with that of a fixed mast. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…On the contrary, changes in the variation of the wind speed V 0 between 2.5 m s −1 and 10 m s −1 result in changes in R/D values up to 80%. The results are compatible with previous experimental studies by e.g., Wilson et al [51]. Despite using a UAV with propellers of 76.2 mm mm diameter, i.e., roughly a factor of 10 smaller than ours, they come to a similar conclusion and showed that the PIF at 5.3 D (roughly 400 mm) above the UAV at the center of the fuselage, has negligible impact on the wind speed measurements.…”
Section: Sensor Placement Studysupporting
confidence: 93%
“…On the contrary, changes in the variation of the wind speed V 0 between 2.5 m s −1 and 10 m s −1 result in changes in R/D values up to 80%. The results are compatible with previous experimental studies by e.g., Wilson et al [51]. Despite using a UAV with propellers of 76.2 mm mm diameter, i.e., roughly a factor of 10 smaller than ours, they come to a similar conclusion and showed that the PIF at 5.3 D (roughly 400 mm) above the UAV at the center of the fuselage, has negligible impact on the wind speed measurements.…”
Section: Sensor Placement Studysupporting
confidence: 93%
“…Remark 4: It is reasonable to use the terminal equality constraint xk+N ℓ |k = 0 in low-level MPC scheme. Because the main task of the low-level controller is to drive the tracking error xk in (14) to zero. Additionally, the terminal equality constraint (15d) can simplify the terminal ingredients of the MPC algorithm largely, for that the calculation of terminal ingredients for timevarying system is quite complex especially for higherorder dynamic system like unmanned aircraft [33], [34].…”
Section: B Stability Analysis Of the Low-level Mpcmentioning
confidence: 99%